Fake Snakes And Weird Wizards - Winkler, Henry 1945-; Oliver, Lin; Garrett, Scott (New York, New York Grosset & Dunlap, an imprint of Penguin Group (USA) LLC, 2015)
"Hank's sister Emily wants Ralph's Reptile Show to perform at her birthday party more than anything, but Ralph is booked solid. So Hank comes up with a plan: he'll disguise himself as a magician called The Westside Wizard and pull a snake from thin air! But when Hank's true identity is revealed during his performance, his good deed might just turn into a huge disaster"--
Keywords: Magic tricks -- Fiction; Birthdays -- Fiction; Parties -- Fiction; Snakes -- Fiction; Family life -- Fiction; Learning disabilities -- Fiction; Humorous Stories; JUVENILE FICTION / Readers / Chapter Books; JUVENILE FICTION / Animals / Reptiles & Amphibians; JUVENILE FICTION / Humorous Stories